Analysis of Environmental Traffic Flow Characteristics on Jalan Kaharuddin Nasution – Marpoyan, Pekanbaru City - Lasmita, Revi; Putri Permata MS, Ayu; Gusnanda (Journal of Engineering Science and Technology Management, 2023)
Jalan Kaharuddin Nasution, a major educational area in Pekanbaru, hosts numerous schools and universities along with various amenities such as hotels, restaurants, cafes, shops, and street vendors. This study focuses on three key traffic components: Speed, Volume, and Density, aiming to analyze service levels on Kaharuddin Nasution Street. The research investigates the relationship between traffic flow components (Volume, Speed, and Density) using the Greenshield and Greenberg Models. Findings reveal that the Greenshield Model best portrays congestion density (Dj), ranging from 103.17 to 126.41 vehicles/km, compared to Greenberg's much higher Dj values (642.89 – 3990.35 vehicles/km). Greenshield also identifies maximum volume/capacity (1801.74 – 2562.53 vehicles/hour), while Greenberg shows higher capacity (3477.38 – 12826.50 vehicles/hour), inconsistent with the road's actual capacity. Service levels on Kaharuddin Nasution Street throughout the week are categorized as E, indicating service levels beyond speed measurement due to consistently lower speeds than level D. Unstable traffic results from near-capacity volumes, causing congestion and occasional standstill. Effective traffic management considering volume, speed, and density is essential to anticipate future congestion issues on Kaharuddin Nasution Street.